PENDAMPINGAN KEPADA MASYARAKAT DESA BELANG KECAMATAN BUNGKAL KABUPATEN PONOROGO DALAM MEWUJUDKAN DESA TANGGUH DI MASA PANDEMI COVID-19 - Moh. Amin; Amrih Yuwono; Abdul Halim (Jurnal Pengabdian Kepada Masyarakat, 2022)
Assistance activities for the Belang village community, Bungkal District, Ponorogo Regency as a mandate of the Tri Dharma College to carry out community service adhering to the village's main activities by providing support and actively participating in realizing the Covid-19 Resilient Village carried out by the Belang Village Government, namely maintaining the economy and maintain public health. In this activity using the PAR (Participatory Action Research) method. In this case, the service team acts as a companion and facilitator who must understand the characteristics and needs of the community. This assistance activity in program preparation is carried out according to the needs of the village community and the ability of the service team so that there is an agreement at the beginning in planning the preparation of the program. Sustainable activities are still carried out because the village community is satisfied with the assistance provided, as well as related to the assistance to the village community for medium and long term food security in the form of fruit plant seeds, namely -/+ 1550 in the form of durian, soursop, avocado, cashew, orange seeds. pamelo, tangerine, jackfruit, ketapang to improve the community's economy so it is necessary for assistance in the medium and long term. The community can increase income by utilizing the results of their fruit plants by adding selling value, for example, realized by ready-to-eat food, juice drinks, etc.